Die toekoms van die Afrikaanse gereformeerde kerke in Suid-Afrika: moontlike, waarskynlike en verkieslike opsies - Tolmay, Barry (Stellenbosch Theological Journal, 2021)
The future of the Afrikaans reformed churches in South Africa: possible, probable and desirable options In 1994, South Africa experienced a radical paradigm shift which in some ways led Afrikaans reformed churches into a state of semi-paralysis. Over the past twenty-six years the church has had to deal with the resultant fallout. The fact that many setbacks had been overcome successfully, is an encouraging indication that the church has the potential of a brighter future. Bosch stated that as long as one lives and thinks within the patterns of a given paradigm, then that paradigm provides one with a plausible structure according to which all reality is interpreted. The quintessential question would be: what is the preferred future vision for the Afrikaans reformed churches? How is the journey to 2030 and 2040 mapped out? These answers will partly determine the outcome. When one evaluates the current situation, both positive and negative aspects have to be considered. The key question is, how can the positives be optimised, and the negatives minimised? With vision and scenario planning and the detailed consideration of possible, probable and preferable outcomes, an exciting future becomes possible. The challenges of membership, finances, consumerism and also Covid-19 can also be overcome. More informal church practises for those on the fringes are opening new opportunities globally - as expressed by for instance the Fresh Expression Movement. A new and vigorous focus on relationships, care, community involvement and friendship missions may result in fulfilling the vision of the Afrikaans reformed churches. With compassion in action, Afrikaans reformed churches can in some ways blossom over the next two decades.